Development Transformation: Strategy for Economic and Social Progress in Indonesia - Karina Tri Ayudiasari; Resa Rosialani; Muhammad Abdan Shidqi Khoerizza (GoResearch - Research & Publishing House, 2023)
Development transformation is often formulated through economic policies in many ways prove success. This can be illustrated, among others, in Singapore, Hong Kong, Australia and other developed countries. Economic policies in these countries are generally formulated conceptually, involving consideration of social and environmental aspects and supported by responsible political mechanisms so that every economic policy can be explained in a transparent, fair manner and accordance with planning principles. In the social aspect, not only are people's aspirations taken into consideration, but also the existence of social institutions (social capital) is also maintained and even their function is improved. Meanwhile, in terms of the environmental aspect, the aspect of the function of preserving natural capital is also given great attention for the benefit of humanity. Of all that, the most important thing is that decision-making is also carried out very cleanly from various lobbying behaviors that have nuances of deficiencies (moral hazard) that are fulfilled by certain interests (vested interests) from mere profits (rent-seeking). In this way, the results of development can be enjoyed by the entire community fairly across (transcending) boundaries of space (inter-region) and time (inter-generation), national development can also be interpreted as deliberate economic, social, and cultural transformation through policies and strategies toward the desired direction. Transformation in economic structure, for example, can be seen through an increase or rapid growth in production in the industrial and service sectors, so that their contribution to national income becomes greater. On the other hand, the contribution of the agricultural sector will become smaller and inversely proportional to the growth of industrialization and economic modernization. Social transformation can be seen through equal access to socio-economic resources, such as education, health, housing, clean water, recreational facilities, and participation in the political decision-making process.